A novel environmental control system facilitating humidification for commercial aircraft. (December 2017) - Chen, Long; Zhang, Xingjuan; Wang, Chao; Yang, Chunxin
Abstract: Extreme aircraft cabin air dryness during cruise has aroused wide concern throughout the past 30 years. A new integrated system featuring air supply, pressure regulation, temperature control, water separation, and cabin humidification is proposed based on numerous field investigations, existing cabin humidification methods, and conventional aircraft environmental control systems. Cabin humidification is realized through the injection of purified water into the suction side of cabin environmental control system compressor without changing the original system structure. Another advantage of the new system is the lower demand of ram air benefitted from the decreased temperature of compressor inlet with water injection process. System analysis models and software using enthalpy parameter method are also presented. Verification experiments focused on the core parts of the integrated system show that the system analysis models agree with the experimental data well. System performance characteristic and fuel penalty are evaluated using thermodynamic analysis parameters. Results show that under 5 g/(kg·dry air) humidification, the cabin humidity increased smoothly to about 27.9% during the cruising state. The fuel penalty decreased by 1% under the new integrated system for the lower demand of ram air. The novel integrated system is effective and economy. Highlights: An integrated environmental control system with humidification is proposed. The new system can increase the cabin's relative humidity during cruise. The novel system lowers ram air demand compared with the conventional. Penalty analysis shows that the new system saves fuel and increases economy.